OPTIMALISASI KUALITAS BALITA MELALUI PENINGKATAN KEMAMPUAN KADER BKB DALAM DETEKSI DINI GANGGUAN PERKEMBANGAN BALITA - Mariyam Mariyam; Vivi Yosafianti Pohan (Universitas Muhammadiyah Semarang, 2017)
RW VI Tembalang Tandang is one of the areas in Semarang City. The efforts to improve the quality of infants in RW VI had been done with the formation of Posyandu, PAUD and Bina Keluarga Balita (BKB). Posyandu had provided services with average growth per month, but not yet developed.Monitoring the development of toddler is expected to be implemented by BKB by using Kartu Kembang Anak (KKA). BKB in RW VI has been doing activities by providing counseling and consultation to parents of children related to growth and development, but the development of toddlers up has not been done. The current Kader BKB also do not understand how to make progress in toddlers. Therefore it isnecessary tips in improving the knowledge, skills and assistance on kader BKB to perform observations of developments in order to adjust the development of toddler in RW VI for optimal quality of toddlers.The purpose of this community service activity is increase the knowledge and ability of Kader BKB in the message of child development. Awareness raising activities of toddler and mentoring in development by using Kartu Kembang Anak (KKA). Approach method was done by lecture, discussion, simulation /game, and role play. The kader are involved in the number of 8 Kader, before the extension activity is done 100% Kader do not know how to fill the KKA, after the implementation of the counseling 100% Kader have known how to fill KKA and know how to interpret the development of children. Keywords: kader BKD, development, toddler